A longitudinal analysis of smoke‐free laws and smoking initiation disparities among young adults in the United States. (18th September 2021) - Titus, Andrea R.; Xie, Yanmei; Thrasher, James F.; Levy, David T.; Elliott, Michael R.; Patrick, Megan E.; Fleischer, Nancy L.
Abstract: Background and Aims: Tobacco control policies may differentially impact smoking initiation among socio‐demographic groups. We measured longitudinal associations between exposure to smoke‐free laws in grade 12 (modal age 18 years) and patterns of smoking initiation in the United States. Design: Prospective longitudinal analysis. Setting and Participants: We used data on US young adults sampled at modal age 18 years from the Monitoring the Future Survey. Baseline data were collected between 2000 and 2017, with the last year of follow‐up in 2018. The sample number varied by outcome and time‐point, ranging from 7314 to 17 702. Measurements: Smoke‐free law coverage in work‐places and hospitality venues (restaurants/bars) was measured as the percentage of the county population covered by each type of law. We examined associations with any past 30‐day smoking initiation and daily smoking initiation at modal ages 19/20, 21/22 and 23/24, using Poisson regression and calculating average marginal effects. We explored effect modification by sex, race/ethnicity and parental education by testing the significance of interaction terms. Findings: Work‐place law coverage at modal age 18 was associated with a lower probability of daily smoking initiation at modal ages 21/22 [−2.4 percentage points (p.p.); 95% confidence interval (CI) = −3.9, –0.9] and 23/24 (−2.0 p.p.; 95% CI = −3.9, –0.2). Hospitality law coverage was associated with a lower probability of daily smoking initiation at modal ages 19/20 (−1.6 p.p.; 95% CI = −2.8, –0.4), 21/22 (−2.3 p.p.; 95% CI = −3.7, –0.9) and 23/24 (−1.8 p.p.; 95% CI = −3.6, –0.0). Findings were inconclusive with regard to associations with any past 30‐day smoking initiation and with regard to effect modification, after adjusting for multiple testing. Conclusions: Exposure to smoke‐free laws at age 18 appears to be prospectively associated with reduced daily smoking initiation 1–6 years later.